Networking issue - Shah, Asadullah; Dwi Handayani, Dini Oktarina (IIUM Press, 2011)
All communication networks use or going to use packet based communications that intrinsically use STDM for communication. No user is going to have a fixed time slot instead, a slot is allocated on a demand basis or activity basis. The packet discarding is a new' concept in networking, in this chapter a random packet discarding is explained.